Helping hands self-initiated cooperating behaviors among preschool children in a public day care center - Dacillo, Janina May J.; Mabanta, Joanne Marie M. (College of Home Economics, University of the Philippines Diliman, 2019)
This study seeks to describe three aspects of cooperating behaviors, namely its nature, manifestations, and factors. It examined its presence among children in a day care center in Marikina City which includes a time for children to play within the week. There were 13 participants aged three and four who were included in the study. Within three weeks, or eight observation sessions, the children were observed in a non-participatory manner. In a week, the children were observed twice during their structured activities and once for their unstructured activities. The researchers used one video camera to record the behaviors, supplemented by running records and anecdotal records to gather data during the sessions. Moreover, to further clarify the definition of cooperating behaviors, the researchers came up with the three features of cooperating behaviors, which includes having the involvement of two or more individuals, with the same goal, and working towards this goal. A total of 107 episodes of cooperating behaviors were found, which were then analyzed using a tool that the researchers made, wherein common goals of the cooperating behaviors were grouped together to create the three categories of cooperating behaviors that manifested in the day care center. From 107 episodes of cooperating behaviors, 51 was attributed to their engagement through materials, 35 manifesting them following the routine, and 21 emerged due to the interaction among children. Through this, it was found how important the presence of materials, variety in activities, close relations, and having a bigger classroom space are in promoting cooperating behaviors among children in the day care center.